Catheter induced aortocoronary dissection during percutaneous coronary intervention: successful aortoostial stenting - Ahmet Gürdal; Süleyman Sezai Yıldız; Kadriye Kılıçkesmez (KARE Publishing, 2018)
Iatrogenic acute dissection of the ascending aorta is a serious but rare complication of cardiac catheterization and percutaneous coronary intervention (PCI). Although treatment of ascending aortic dissection may require surgical repair, stenting at the origin of the dissection area may be sufficient in aortocoronary dissection (AD) following PCI. Described is the case of a 64-year-old female patient who was treated with PCI for a critical lesion of the right coronary artery (RCA). Immediate stenting at the source of the dissection was sufficient to repair the RCA lesions and successfully seal the site of retrograde propagation of the dissection. The ascending aortic dissection was monitored with computed tomography and the dissection was spontaneously repaired within 72 hours.